ANALYSIS OF CURRENT SITUATION AND HEALTH MEASURES UNIVERSITY TEACHERS IN BEIJING - Wei, Luo; Hongwei, Yan; Senja, Qonidah Salsabila (Universitas Pendidikan Indonesia, 2022)
This study mainly uses the methods of questionnaire and interview to investigate the fitness status of 291 teachers in a sports college in Beijing. The purpose in this study to understand and grasp the current fitness situation of teachers in a sport college in Beijing, find out the main problems, and put forward corresponding countermeasures, so as to provide theoretical reference for relevant departments of the school. It is found that the number of male teachers participating in fitness is far less than that of female teachers; The number of administrative personnel participating in fitness activities is large, and the number of discipline and technical teachers participating in teaching posts is small; In service teachers have heavy work tasks and family burdens, and their time for physical fitness activities is relatively limited; Teachers generally have a high understanding of the national fitness plan (2016-2020); It is common for teachers to work overtime. More than 75% of teachers need to work overtime every week. Conclusion: the health status of college teachers in a physical education college in Beijing is not optimistic; High quality sports fitness venue resources ensure the smooth development of teachers' fitness activities; The school's professional organization of fitness activities is deeply welcomed by teachers; The publicity of physical fitness activities is not enough, and the number of teachers participating in fitness activities is small.